2021
DOI: 10.1038/s41598-021-85391-3
|View full text |Cite
|
Sign up to set email alerts
|

Unimanual and bimanual motor performance in children with developmental coordination disorder (DCD) provide evidence for underlying motor control deficits

Abstract: Much of our understanding of motor control deficits in children with developmental coordination disorder (DCD) comes from upper limb assessments focusing on the dominant limb. Here, using two robotic behavioural tasks, we investigated motor control in both the dominant and non-dominant limbs of children with DCD. Twenty-six children with diagnosed DCD (20 males; mean age 10.6 years ± 1.3 years) and 155 controls were included in this cross-sectional study. Participants completed a visually guided reaching task … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…The advent and advancement of robotics have enabled the development of tasks that humans cannot perform, or at least not with such precision [66][67][68]. In the field of eHealth, robotics has played a fundamental role in helping and treating people with various neurological conditions such as trauma [69], dementia [33][34][35][36][37], ASD [24][25][26][27][28], cerebral palsy [29][30][31][32] and ADHD [18][19][20][21][22][23]. Although in recent years the application of robotics in the treatment and support of ADHD has received considerable research attention, however, it is far inferior compared to dementia, autism, and cerebral palsy.…”
Section: Evolution Of Robotic Application In Adhd Treatmentmentioning
confidence: 99%
See 2 more Smart Citations
“…The advent and advancement of robotics have enabled the development of tasks that humans cannot perform, or at least not with such precision [66][67][68]. In the field of eHealth, robotics has played a fundamental role in helping and treating people with various neurological conditions such as trauma [69], dementia [33][34][35][36][37], ASD [24][25][26][27][28], cerebral palsy [29][30][31][32] and ADHD [18][19][20][21][22][23]. Although in recent years the application of robotics in the treatment and support of ADHD has received considerable research attention, however, it is far inferior compared to dementia, autism, and cerebral palsy.…”
Section: Evolution Of Robotic Application In Adhd Treatmentmentioning
confidence: 99%
“…Motor control deficits in children with ADHD are known to come from the upper limb, specifically the dominant limb [99]. The study [22] used two robotic behavioral tasks to investigate motor control in the dominant and nondominant limbs of children with DCD. Twenty-six children with ADHD, learning disorder (LD), or generalized anxiety disorder (GAD) were evaluated by a registered healthcare provider in 155 controls.…”
Section: B Motorskills Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…When considering voluntary movements, children with DCD appeared able to programme their movement accurately in easy end-state-comfort tasks, while they displayed difficulties in complex tasks (Adams et al, 2017; Noten et al, 2014; Smyth & Mason, 1997). In visually guided reaching tasks, their initial direction error has been found unaffected – attesting of preserved feedforward control, while the path length could be longer in children with DCD than in TD children – suggesting that they reached for a longer than necessary distance, which could highlight deficits in integrating visual information and online control (Grohs et al, 2021). Regarding the feedback control, children with DCD were found impaired in rapid online control (ROC) through double-step paradigms (Hyde & Wilson, 2011a, 2011b; but see Adams et al, 2017 for absence of ROC deficit).…”
Section: Introductionmentioning
confidence: 99%
“…Common kinematic measures include movement trajectory, time, velocity, and normalized jerk [28][29][30]. Previous studies showed that DCD children performed with slower reaction times, larger endpoint errors, longer movement and/or deceleration times with more curved trajectories, and showed greater variability in movement speed compared to TD children in upper limb tasks [27,31]. Normalized jerk (NJ), which is often used to measure movement smoothness [30,32,33], was found in children with and without DCD to have the same developmental trajectory; however, when controlled for age, children with DCD exhibited greater NJ in upper limb movement [34].…”
Section: Introductionmentioning
confidence: 99%